Snapshots in surgery: small bowel intussusception following ileojejunal bypass. Issue 6 (4th September 2014) - Ward, Joseph; Jaber, Basel; Leaman, Charlotte; Barry, Jonathan; Khot, Umesh
Key Clinical Message Jejunal intussusception is a known complication of ileojejunal bypass surgery for obesity that may present as an acute abdomen. It can be avoided if the jejunum is anchored to the transverse mesocolon intra‐operatively.